Coordinating Service Compositions : Model and Infrastructure for Collaborative Creation of Electronic Documents (2019)
Electronic documents frequently include contributions from different human and non-human sources. The Web, for instance, offers ever-changing content and services which can perform activities during document creation. This thesis introduces a solution for collaborative document creation which maps contributions of human and non-human participants to software services. The joint flexible composition and coordination of these services leads to a novel understanding of dynamic Web-based documents.